2023
DOI: 10.1111/sum.12997
|View full text |Cite
|
Sign up to set email alerts
|

Combined biochar and manure addition to an agricultural soil benefits fertility, microbial activity, and mitigates manure‐induced CO2 emissions

Manhattan Lebrun,
Zubda Zahid,
Magdalena Bednik
et al.

Abstract: The importance of blending biochar into manure prior to its application as a soil amendment was investigated by this laboratory and field study, hypothesizing an (i) increase in soil fertility; (ii) improvement in microbial activity; (iii) reduction in manure‐induced CO2 emissions after combining amendments. Biochar was mixed with manure (50:50 V/V) and aged in field conditions for 6 months whereafter pristine biochar, manure, and manured biochar (50:50 V/V) were incorporated into an agricultural drought‐prone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…Mycorrhiza, but also microorganisms involved in essential nutrient cycling processes, such as (de)nitrification, phosphate solubilization and carbon and nitrogen mineralization (Enaime & Lübken, 2021;Yadav et al, 2021) abundance and activity of soil microorganisms likely contributed to the overall enhancement in nutrient availability. Long-term release of nutrients, as well as enhancement of AMF, are in accordance with previous studies, which demonstrated increased water retention, better nutrient retention and enhanced microbial activity (Lebrun et al, 2022(Lebrun et al, , 2024Seyedsadr et al, 2022). This study's findings hold particular importance in the context of N and P, two elements often deficient in arable soils.…”
Section: Benefits Of Biochar-based Materials On Soil Fertilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Mycorrhiza, but also microorganisms involved in essential nutrient cycling processes, such as (de)nitrification, phosphate solubilization and carbon and nitrogen mineralization (Enaime & Lübken, 2021;Yadav et al, 2021) abundance and activity of soil microorganisms likely contributed to the overall enhancement in nutrient availability. Long-term release of nutrients, as well as enhancement of AMF, are in accordance with previous studies, which demonstrated increased water retention, better nutrient retention and enhanced microbial activity (Lebrun et al, 2022(Lebrun et al, , 2024Seyedsadr et al, 2022). This study's findings hold particular importance in the context of N and P, two elements often deficient in arable soils.…”
Section: Benefits Of Biochar-based Materials On Soil Fertilitysupporting
confidence: 92%
“…The effects of biochar also appear universal. In light sandy soils with a limited amount of organic matter, biochar leads to improved soil water and nutrient retention (Lebrun et al, 2022(Lebrun et al, , 2024Seyedsadr et al, 2022), whereas in heavy clay soils, biochar aids aeration and increases soil permeability by lowering bulk density.…”
Section: Benefits Of Biochar-based Materials On Soil Fertilitymentioning
confidence: 99%